2012
DOI: 10.1111/j.1540-6210.2012.02616.x
|View full text |Cite
|
Sign up to set email alerts
|

Place, Time, and Philanthropy: Exploring Geographic Mobility and Philanthropic Engagement

Abstract: America is a nation of movers, and this has implications for public and nonprofit managers who rely on donations and volunteers to increase the capacity of nonprofits and to strengthen local communities. This article explores the impact of time and place on philanthropic engagement, focusing on how three aspects of community—sense of belonging, social connections, and regional culture—are related to volunteering and giving to local organizations. The authors find that geographic mobility affects philanthropic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
1
13
0
1
Order By: Relevance
“…Findings from this study add to the work by other scholars supporting regional differences in nonprofit organizations and philanthropy (Schneider, 1996;Clerkin, et al, 2013) and in historic preservation (Carlson, 1980). It also supports studies that have found differences in behaviors in nonprofit organizations related to decision-making rationale (Bromley, Hwang, & Powell, 2012).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Findings from this study add to the work by other scholars supporting regional differences in nonprofit organizations and philanthropy (Schneider, 1996;Clerkin, et al, 2013) and in historic preservation (Carlson, 1980). It also supports studies that have found differences in behaviors in nonprofit organizations related to decision-making rationale (Bromley, Hwang, & Powell, 2012).…”
Section: Discussionsupporting
confidence: 84%
“…In the United States, regional designations are employed to better understand differences in policies and actions of government and nonprofit organizations (Schneider, 1996;Clerkin, Paarlberg, Christensen, Nesbit, & Tschirhart, 2013). Carlson (1980) analyzes historic preservation by region using National Register data coded into 10 different building types and finds that eastern states have a higher concentration of sites on the register than Western states.…”
Section: Regionalism: Differing Regional Climates Lead To Regional Vamentioning
confidence: 99%
“…Using data from a survey of residents in southeastern North Carolina, Clerkin, Paarlberg, Christensen, Nesbit, and Tschirhart published a study in 2013 examining the impact of participants' -sense of community,‖ social ties, and their regional culture on their charitable giving [18]. Regarding culture, regional cultural perspectives tend to vary regarding the role of government verses nonprofit civic organizations in meeting community needs.…”
Section: Past Researchmentioning
confidence: 99%
“…For example, Putnam reported that every 10 minutes of commuting resulted in a 10% reduction in social connectedness in local communities (Putnam, 2000, p. 204). Similarly, other studies have suggested that long commuting hours lower the sense of community (Clerkin et al, 2013), discourage social trust at the local level (Williamson, 2002), and decrease local participation in sharing, donating, or volunteering (Corporation for National and Community Service & National Conference on Citizenship, 2010).…”
Section: Commuting and Local Community Engagement: Time Resource–based Approach And Place Identity–based Approachmentioning
confidence: 97%
“…One of the natural outcomes of the detachment between place of residence and place of work is an increasing number of people who have to commute. Many previous studies have claimed that commuting has detrimental effects on community engagement or community-level social capital (Clerkin, Paarlberg, Christensen, Nesbit, & Tschirhart, 2013; Kang & Kwak, 2003; Shah, McLeod, & Yoon, 2001). Since the late 19th century, urban commuters have been described as having decreasing commitment to their neighborhoods (Balderstone, 2014, p. 142).…”
mentioning
confidence: 99%